2019
DOI: 10.1007/978-3-030-30244-3_25
|View full text |Cite
|
Sign up to set email alerts
|

Path Planning Algorithms Benchmarking for Grapevines Pruning and Monitoring

Abstract: Labour shortage is a reality in agriculture. Farmers are asking for solutions to automate agronomic tasks, such as monitoring, pruning, spraying, and harvesting. The automation of these tasks requires, most of the time, the use of robotic arms to mimic human arms capabilities. The current robotic arm based solutions available, both in the market and in the scientific sphere, have several limitations, such as, lowspeed manipulation, the path planning algorithms are not aware of the requirements of the agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The results indicated a comparison of efficiency and repeatability of particular planners for a planning scene imitating conditions in a greenhouse or similar pick-and-place tasks. Magalhães et al [11] suggested benchmarking path planner algorithms from Open Manipulator Planning Library (OPML) for tree pruning tasks. Thus, the results demonstrated good agreement for the BiTRRT algorithm compared with other algorithms from the OMPL library, such as BKPIECE, LBKPIECE, SBL, and others.…”
Section: A Motion Planning Benchmarkingmentioning
confidence: 99%
“…The results indicated a comparison of efficiency and repeatability of particular planners for a planning scene imitating conditions in a greenhouse or similar pick-and-place tasks. Magalhães et al [11] suggested benchmarking path planner algorithms from Open Manipulator Planning Library (OPML) for tree pruning tasks. Thus, the results demonstrated good agreement for the BiTRRT algorithm compared with other algorithms from the OMPL library, such as BKPIECE, LBKPIECE, SBL, and others.…”
Section: A Motion Planning Benchmarkingmentioning
confidence: 99%
“…The robotic system and manipulator are show in Figures 1 and 2, respectively. Magalhães et al (2019) benchmarked different path planning algorithms on a simulated pruning manipulator with a mobile base, based on an existent manipulator, shown in Figure 3, for pruning grapevines in steep slope vineyards. The manipulator is a 6 DoF Robotis Manipulator-H.…”
Section: Robotic System To Prune Grape Vinesmentioning
confidence: 99%
“…Additionally, it was verified that these manipulators present challenges concerning path planning. Although Magalhães et al (2019) successfully planned the path for a manipulator using different algorithms, it took much longer than a human would take to determine a path. You et al (2020) managed to obtain lower planning times, but their manipulator took a high amount of time to execute the path, making it also inefficient when compared to a human.…”
Section: Analysis and Comparisonmentioning
confidence: 99%
“…An integrated pruning robotic system may consist of cameras, manipulators, a computer, sensors, and a cabin platform containing other system parts and straddling the vine row [3,4]. Few studies have been reported on a robotic pruning system [3,[5][6][7][8][9][10], most of which did not focus on the manipulators' mechanical design-which can significantly enhance the manipulator's operational performance-and rather concentrated on machine vision, algorithm design, and path planning issues. Furthermore, a cane pruning robot has never been designed; the main focus of previous studies was on spar pruning [3,9].…”
Section: Introductionmentioning
confidence: 99%